2022
DOI: 10.1007/s11116-022-10293-w
|View full text |Cite
|
Sign up to set email alerts
|

Stated benefits of teleworking in Mexico City: a discrete choice experiment on office workers

Abstract: Commuting is expensive in megacities of emerging economies. By decreasing work-related trips, teleworking may reduce congestion and commuting time. Taking Mexico City’s office workers’ as case study, this paper reports findings from a discrete choice experiment (DCE) exploring willingness to see a cut in monthly paycheck in exchange for teleworking two days a week from a shared office. This DCE explores preferences for bike parking spaces at shared office’s facilities, and walking commuting time to shared offi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Related to both results, in a research during the pandemic, Mihalca et al (2021) found “that good physical conditions and adequate telework tools would be positively related to job performance and satisfaction with telework” (p. 631). Now, to guarantee a good place for teleworking and improve job satisfaction and productivity, organizations could adapt space in the teleworker’s home, or rent spaces for teleworking in a shared co-working office, which, according to Lara-Pulido and Martinez-Cruz (2022) is an attractive alternative for office workers in Mexico even before COVID-19, where employees were willing to pay due to the benefits in terms of time and cost that it brings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Related to both results, in a research during the pandemic, Mihalca et al (2021) found “that good physical conditions and adequate telework tools would be positively related to job performance and satisfaction with telework” (p. 631). Now, to guarantee a good place for teleworking and improve job satisfaction and productivity, organizations could adapt space in the teleworker’s home, or rent spaces for teleworking in a shared co-working office, which, according to Lara-Pulido and Martinez-Cruz (2022) is an attractive alternative for office workers in Mexico even before COVID-19, where employees were willing to pay due to the benefits in terms of time and cost that it brings.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the possibility of the working day being extended and productive and domestic work being interspersed ( Bosch et al, 2020 ). Teleworking has also increased gender differences regarding the division of activities at home ( Villarreal, 2020 ; Lara-Pulido and Martinez-Cruz, 2022 ). This leads to negative consequences for both the company and the workers, producing low productivity on workers ( Kossek and Ozeki, 1999 ), which would also affect their levels of job satisfaction ( Kossek and Ozeki, 1998 ; Hernández, 2019 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Anderson et al (2015) found that there can be substantial benefits from home working, but note that the effects may vary between different types of people. Lara-Pulido and Martinez-Cruz (2022) show that workers have a substantial willingness to pay in order to be able to work at least some of the time from home.…”
Section: Introductionmentioning
confidence: 99%
“…Government organisations and managers must follow the implementation and observance of appropriate clauses in employment contracts that clearly and correctly regulate working conditions, implicitly respecting the rights and obligations of the parties engaged in telework. Other studies have demonstrated the multiple advantages of telework, such as increased flexibility, cost savings, improved productivity, job satisfaction and retention (Zalat and Bolbol, 2022; Lara-Pulido and Martinez-Cruz, 2022). Our findings indicate the need to change working conditions to support the performance and efficiency of telework by changing and updating ICT, but also by increasing the protection, safety and health of employees.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%